DISTRIBUTION OF THE BURDEN PROOF AS A GUARANTEE OF WORKER’S ACCESS TO LABOR JUSTICE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The Democratic State of Law demands that the citizens have adequate access to justice, besides the existence of a jurisdictional institution to protect their rights. In the labor scenario, the mechanism which ensure the parity of processual opportunities becomes an essential element to access to the intended judicial protection, considering the disparity of powers between the parts in the labor’s process. In this regard, the research problem of the present study is to analyze the question: how does the inversion of the burden of proof guarantees the access of the workers to the labor justice? The search to answer this question is the main objective of the article. Thus, the study utilizes the deductive method, by analyzing two correct premises, a major and a minor, correlating them logically. The methodological procedure adopted by the study is the bibliographical and documental research. In conclusion, it is verified that the innovations brought by the Labor Reform regarding this aspect were beneficial for allocating more legitimacy the judge’s decision making when determining the inversion of the burden proof.